Beyond procedural ethics: Foregrounding questions of justice in global health research ethics training for students - Hunt, Matthew R.; Godard, Beatrice (Global public health, 2013)
Interest in global health is growing among students across many disciplines and fields of study. In response, an increasing number of academic programmes integrate and promote opportunities for international research, service or clinical placements. These activities raise a range of ethical issues and are associated with important training needs for those who participate. In this paper, we focus on research fieldwork conducted in lower income nations by students from more affluent countries and the ethics preparation they would benefit from receiving prior to embarking on these projects. Global health research is closely associated with questions of justice and equity that extend beyond concerns of procedural ethics. Research takes place in and is shaped by matrices of political, social and cultural contexts and concerns. These realities warrant analysis and discussion during research ethics training. Training activities present an opportunity to encourage students to link global health research to questions of global justice, account for issues of justice in planning their own research, and prepare for 'ethics-in-practice' issues when conducting research in contexts of widespread inequality. Sustained engagement with questions of justice and equity during research ethics training will help support students for involvement in global health research.